Control interno del área de bodega de la Empresa Naturisa S.A. de la ciudad de Guayaquil, período 2023. - Torres Rengifo, Luis Alfredo (2025)
The present study is based on the analysis of the internal control of the warehouse area of the company NATURISA S.A of the city of Guayaquil based on the COSO internal control model, determining the components of this control model, with the purpose of evaluating its development. and application within the warehouse area, and in relation to this evaluation determine the level of risk and confidence present in each component of the control model. For the development of the study, methodologies and tools were used that enabled the analysis of each of the components of the COSO internal control model, supporting the analysis of the results for the preparation of focused and appropriate conclusions and recommendations that constitute an option for the strengthening of the internal control mechanisms in the warehouse area of the company NATURISA S.A, necessary for the achievement of the set objectives and the reduction of risk within the activities and their optimal development. Highlighting the importance of internal control and its determining value for the company in order to achieve the proposed objectives.